TRADISI BURDE’EN DALAM MENANGANI COVID-19 DI DUSUN SAPA’AH DESA KOMBANGAN - Ummu Kulsum, Roudlotul Jannah; Moh. Abdulloh Hilmi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
Burde'en (recitation of salawat burdah around the hamlet every night) which was initiated by religious elites (ustaz, kiai) in Sapa'ah Hamlet, Bangkalan, Madura was carried out to deal with Covid-19. The implementation of this tradition is contrary to the provisions of the government's health protocol which is based on a medical approach even though it appears with the same goal: eradicating Covid-19. In fact, this tradition actually triggers crowds, not wearing masks, and so on. So, the question to be answered in this study is: